Design and Stiffness Analysis of the Partial-face TBM Propulsion Mechanism - Cui Guangzhen; Lu Hua; Xiao Yanqiu; Cen Yaping; Sun Chunya; Wang Pengpeng (Jixie chuandong)
Aiming at the weak stiffness of the series support mechanism of the partial-face boring machine, poor adaptability of the non-circular TBM section, and difficulties in dealing with the blind area of excavation, a partial-face TBM propulsion mechanism based on the 6-SPS parallel mechanism is designed, and a stiffness prediction model establishment method considering the local flexibility of the platform is proposed. Firstly, the geological conditions is selected, the propulsion reaction force is calculated according to the total thrust prediction model, and the propulsion mechanism is designed. On the basis of inverse kinematics; the rectangular coordinate boundary search method is used to calculate the position workspace of the mechanism. Then, by deriving the micro-displacement mapping between branch chain and the platform, the branch chain is considered, the gravity of the moving platform is regarded as an external load, and the finite element software is used to identify the flexibility coefficient at the contact point between the platform and the branch chain; a semi-analytical static stiffness model of the propulsion mechanism is established, which is verified by the finite element software. Finally, the influence of the local flexibility of the platform on the stiffness performance is compared and analyzed, and the results show that the stiffness model considering the local flexibility of the platform is more accurate. This study provides a theoretical basis for the design and development of the partial-face TBM propulsion mechanism.